The Role of Arabic in Strengthening Cultural Identityin the Digital Age - Retisfa Khairanis; Muhammad Aldi (Universitas Serambi Mekkah, 2025)
This research aims to explore the role of Arabic in strengthening cultural identity in the digital era. The scope of the research includes analyzing the use of Arabic in social media, educational platforms, and other digital content that has an effect on strengthening the cultural identity of Arab and Muslim communities. The method used is a qualitative approach with in-depth interviews involving respondents from various cultural backgrounds and ages. The results show that Arabic not only serves as a means of communication, but also as a symbol of identity that strengthens the sense of community among the community. The use of Arabic in digital content increases cultural awareness and promotes traditional values amidst globalization. In addition, the study found that the younger generation is more active in using Arabic in digital contexts, which has a positive impact on language and cultural preservation. The conclusion of this study confirms that Arabic has a strategic role in strengthening cultural identity in the digital age, with the potential to be a bridge between tradition and modernity. Further efforts are needed to maximize its impact in a global context. Keywords: Arabic Language; Cultural Identity; Digital Age